Kode Etik Jurnalistik sebagai Pedoman Etik Wartawan - Misroji Misroji (STID DI AL-HIKMAH, 2016)
Journalistic Code of Ethics is a guideline of conduct for journalists, of the process of reporting to writing news. He is associated with the problem of ethical values ??are not in the form of criminal sanctions, but moral. However, the Code concerning the integrity and credibility of the journalist or the media where he ruled. Unfortunately, opening the era of freedom that began with the reform does not render the Journalistic Code of Ethics as a guideline strongly held by the women of the media. Over time, the Code rather than decreased, the case is still high even every year. The fact that cases of violation of the Code of Journalism still high it should be a concern of people engaged in the world press. Not only journalists who are parties that directly interact with sources of news, but also other stakeholders such as media owners, to understand and commit to upholding journalistic ethics.